HUBUNGAN KUNJUNGAN ANTENATAL CARE DENGAN KEJADIAN ANEMIA PADA IBU HAMIL - Ditya Yankusuma Setiani; Anisa Galih Pratiwi (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2019)
Background: Anemia in pregnancy is a decrease in hemoglobin levels occurring during pregnancy due to iron deficiency or folate deficiency. In Sukoharjo Regency in 2013 the number of pregnant women reached 14,966 people, and pregnant women suffering from anemia were 1,031 people or 6.8% of the number of pregnant women. The results of a preliminary study conducted in the Tawangsari Village Midwife found 10 people who had anemia. At the interview with 10 pregnant women, 3 answered saying they were not regular in carrying out pregnancy examinations. Purpose and benefit: To determine the relationship between antenatal care and the incidence of anemia in pregnant women in Pranan Village. The benefit of research is to develop and add to existing knowledge about the relationship between antenatal care visits and the incidence of anemia. The subject of study: 32 third trimester pregnant women in Pranan Village Method The research: Used descriptive analytic method with cross sectional approach. This study to determine the factors associated with the incidence of anemia in pregnant women. Sampling in total sampling. The data obtained were analyzed by Chi Square test with p = 0.05. The Result of Research: The study used a method using cross sectional. This study was to determine the relationship between antenatal care visits and the incidence of anemia. Sampling in total sampling. The data obtained were analyzed by Chi Square test with p = 0.05. Conclusion: There was no association between antenatal care visits and the incidence of anemia. Keywords: Anemia, Pregnant Women, Antenatal Care Visits